Smart Cloud of Things: An Evolved IoT Platform for Telco Providers - Antunes, Mário (2016)
Although many environments are powered by smart solutions, users do not have a simple way to gather their collective knowledge and program devices’ behaviour. Telecommunication (Telco) providers wish to act as the facilitator, but still lack proper components for enabling integrated services over their networks, even though this work is already in active standardisation. In this work we present the architecture of a IoT solution developed in close collaboration with Telco providers, its evolution, which we call SCoT (Smart Cloud of Things), and the best practices from the several pilots we have been running. The architecture builds upon ETSI standards, combined with a rich service execution environment, providing facilitated orchestration of services and devices, as well as integrated portals for end users access.